Child Involvement in Family Financial Management and Subjective Well-Being of Children from the Intact and Non-Intact Families - Leti Nurhayati; Istiqlaliyah Muflikhati (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2020)
The purpose of this research is to analyze the influence of child involvement in family financial management and material well-being on children’s subjective well-being among children from intact families and non-intact families. Fifty students from intact families and fifty students from the non-intact family have participated in this research. The students were selected using stratified random sampling techniques from junior high schools in Bogor Regency. Data were collected using a self-administered questionnaire and were followed with in-depth interviews with some students. The result of this research showed that child involvement, material well-being, and subjective well-being were categorized as medium. The result of the independent sample T-test showed that there were no significant differences between students from intact families and students from non-intact families in terms of their involvement in family financial management, material well-being, and subjective well-being. The result of the multiple linear regression test showed that child involvement in family financial management significantly positively affected their subjective well-being. Thus, the higher the children involved in family financial management, the better their subjective well-being.